A meta-analysis of motivational interviewing process: Technical, relational, and conditional process models of change - Magill, Molly; Apodaca, Timothy R; Borsari, Brian; Gaume, Jacques; Hoadley, Ariel; Gordon, Rebecca E F; Tonigan, J Scott; Moyers, Theresa (Journal of consulting and clinical psychology, 2018)
In the present meta-analysis, we test the technical and relational hypotheses of Motivational Interviewing (MI) efficacy. We also propose an a priori conditional process model where heterogeneity of technical path effect sizes should be explained by interpersonal/relational (i.e., empathy, MI Spirit) and intrapersonal (i.e., client treatment seeking status) moderators. A systematic review identified k = 58 reports, describing 36 primary studies and 40 effect sizes (N = 3,025 participants). Statistical methods calculated the inverse variance-weighted pooled correlation coefficient for the therapist to client and the client to outcome paths across multiple target behaviors (i.e., alcohol use, other drug use, other behavior change). Therapist MI-consistent skills were correlated with more client change talk (r = .55, p < .001) as well as more sustain talk (r = .40, p < .001). MI-inconsistent skills were correlated with more sustain talk (r = .16, p < .001), but not change talk. When these indicators were combined into proportions, as recommended in the Motivational Interviewing Skill Code, the overall technical hypothesis was supported. Specifically, proportion MI consistency was related to higher proportion change talk (r = .11, p = .004) and higher proportion change talk was related to reductions in risk behavior at follow up (r = -.16, p < .001). When tested as two independent effects, client change talk was not significant, but sustain talk was positively associated with worse outcome (r = .19, p < .001). Finally, the relational hypothesis was not supported, but heterogeneity in technical hypothesis path effect sizes was partially explained by inter- and intrapersonal moderators. This meta-analysis provides additional support for the technical hypothesis of MI efficacy; future research on the relational hypothesis should occur in the field rather than in the context of clinical trials. (PsycINFO Database Record